Interleukin-2 Receptor Serum Concentrations in Normal Pregnancy and Pre-Eclampsia - Romero Adrián, Tania; Ruíz, Ana; Molina Vílchez, Rafael; Estévez, Jesús; Atencio, Ricardo (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Caslon224 Bk BT"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"Times New Roman"; mso-font-charset:0; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>The purpose of this research was to assess interleukin-2 receptor serum levels in normal pregnancy and pre-eclampsia. Sera from 90 healthy pregnant women (30 for each trimester), 30 with pre-eclampsia and a group of 30 healthy non-pregnant were analyzed. Soluble interleukin-2 receptor was measured by specific double antibody enzymatic immunoassay (ELISA). Results were: 267.5 Ó 12.3 (mean Ó s.e.m) pg/mL in the uncomplicated first trimestre sample, 300.9 Ó 14.5 pg/mL in the second trimester and 248.8 Ó 12.5 pg/mL in the third. The non-pregnant control group had 443.7 Ó 39.6 pg/mL, significantly different from normal pregnancy in all trimesters (p < 0.001). The concentration in pre-eclamptic patients was 382.2 Ó 24.2 pg/mL, with p < 0.01 with regard to the normal third trimester group. The conclusion is that interleukin-2 receptor serum levels diminish in normal pregnancy and rise in preeclampsia. The first finding seems to be a protective mechanism to the fetal allograft. The latter, point to increased cellular activity